Computer program for analysis and design of nanostructured semiconductor devices - Tanaka, Roberto Yuji (2013)
This work presents the recent improvements in a computer program created to assist the design and analysis of quantum well, wire, and dot nanostructured semiconductor-based devices. The list of added features includes the calculation of heavy hole, light hole and split-off energy bands, dark current, photocurrent, and absorption spectrum. Additionally, the computer program allows self-consistent computation and can take into account the energy band non-parabolic effects in the effective mass approximation. © 2013 IEEE.